(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
In this era cancer is biggest problem for human resource and there is multiple type of cancer like blood cancer, breast cancer etc. but here we are talk about only breast cancer. Breast cancer is generally faced by women. Every year the cases of breast cancer increase rapidly and as well as death rate also. The breast cancer is the cause of death in women worldwide. To make breast cancer prediction model is a very challenging task because high accuracy in prediction is very important to know the actual condition or results in the form of chances of survival. Through Machine Learning the prediction and early diagnosis can be easy by using different techniques and algorithms of Machine Learning. But here we use classification method to predict the breast cancer.